New Political Empowerment: Transcending Discourse Contestation between Caring versus Subjugation - Tohari, Amin (Political Science Program, Universitas Negeri Semarang, 2020)
This article focuses on political empowerment discourse between caring politics versus subjugation politics. Through a literature study on empowerment, the writer finds that the empowerment realm has been in a tension between a group that perceives it as a caring action against another group that understands it as a subjugation. Each group has been developing arguments that support their perspective on empowerment. For the group that supports empowerment as caring action, the most important thing is an achievement. They scrutinize the indicators of success and failure, best practices, lessons learned, and many others. On the other hand, the group that views empowerment as subjugation considers it is inherently oppressive. Empowerment is nothing more than a veil that covers the power interest in disciplining poor people to conform to certain standards. Therefore, it is imperative to have a more transformative paradigm to see empowerment as emancipatory politics.